Exploring the use of health and wellbeing measures during pregnancy and the first year following birth in women living with pre-existing long-term conditions: qualitative interviews with women and healthcare professionals - Laura Kelly; Jennifer J. Kurinczuk; Oliver Rivero-Arias; Ray Fitzpatrick; Elizabeth Gibbons; Fiona Alderdice (BMC, 2021)
Abstract Background One way in which care for pregnant and postpartum women living with long-term health conditions (LTCs) may be improved is through the adoption of standardised measures to provide evidence of health outcomes and wellbeing from the woman's perspective. Aim The study explores the views of pregnant and postpartum women living with LTCs, and healthcare professionals to better understand the potential value of using standardised health and wellbeing measures within this patient population. Methods Qualitative semi-structured telephone interviews were conducted to explore the perceived value of using measures with pregnant and postpartum women living with LTCs within maternity services. Participants were asked to provide feedback on three exemplar measures: the Long Term Conditions Questionnaire, the Wellbeing in Pregnancy Questionnaire and the EuroQol EQ-5D-5L instrument. Thematic analysis was used in the analysis of the transcripts. Results Eleven women and 11 healthcare professionals took part in semi-structured interviews. Analysis identified five themes as relevant to the use of measures within maternity services: 1) Improving care, 2) Assessing outcomes, 3) Interpretation and application of data, 4) Engagement challenges and implementation and, 5) Women and healthcare professionals alignment. Conclusions Despite varying prior experience and expressing some questions about implementation, respondents were cautiously positive about the use of standardised health and wellbeing measures. Their use offers the opportunity for both affected women and healthcare professionals caring for them to collectively identify and assess important areas of unmet needs and improve outcomes. Incorporating the perspectives of women with LTC's will help bring awareness to elements of women centred care which health services may seek to address.